Peningkatan Kualitas Pembelajaran IPS melalui Model Pembelajaran Kooperatif Tipe Bamboo Dancing - Romanna Sitindaon (Universitas Negeri Medan, 2017)
The purpose of this study is to improve teacher skills, student activities and student learning outcomes after the teacher using cooperative learning model type Bamboo Dancing in social studies learning in fourth grade students at SD Negeri 101768 Tembung. This type of research is a classroom action research (PTK) consisting of 3 cycles, each cycle consisting of PTK stages. The population in this study were all students of class IV-A which amounted to 27 students. Data analysis techniques used are qualitative and quantitative. Based on data of research result there is improvement of learning quality of IPS. The skills of teachers experienced an increase in cycle I obtained an average score of 2.6, cycle II to 3.2 and cycle III increased to 3.8. Student activity also shows an increase, in cycle I get average score 2,3, cycle II score average 2,6 then cycle III average score reaches 3.5. Percentage mastery learning students also experienced an increase in the first cycle reached 44%, 67% cycle II and 93% 93% cycle. Thus it can be concluded that through cooperative learning model type Bamboo Dancing can improve the quality of learning that includes teacher skills, student activities, and student learning outcomes in the IPS Subject.